2021
DOI: 10.1002/smll.202008210
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Nanomedicine Significantly Enhances the Survival Benefit of Radiation Cancer Therapy by Mitigating Oxidative Stress‐Induced Side Effects

Abstract: Oxidative stress‐induced off‐target effects limit the therapeutic window of radiation therapy. Although many antioxidants have been evaluated as radioprotective agents, none of them are in widespread clinical use, owing to the side effects of the antioxidants themselves and the lack of apparent benefit. Aiming for a truly effective radioprotective agent in radiation cancer therapy, the performance of a self‐assembling antioxidant nanoparticle (herein denoted as redox nanoparticle; RNP) is evaluated in the loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…Metal nanoparticles (NPs) in the tumor volume can serve as sensitizers for enhancing radiotherapy (RT) efficiency. [ 1–10 ] The basis for combining RT with NPs was formed by the pioneering work of Hainfeld and Slatkin in 2004, in which the authors irradiated thiol‐glucose ligand coated gold nanoparticles (Au NPs) with X‐rays. The Au NPs having sizes of 1–3 nm were intravenously injected into EMT‐6 (breast cancer tumor cells), and an 86% increase in the long‐term survival of the animals was proven.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal nanoparticles (NPs) in the tumor volume can serve as sensitizers for enhancing radiotherapy (RT) efficiency. [ 1–10 ] The basis for combining RT with NPs was formed by the pioneering work of Hainfeld and Slatkin in 2004, in which the authors irradiated thiol‐glucose ligand coated gold nanoparticles (Au NPs) with X‐rays. The Au NPs having sizes of 1–3 nm were intravenously injected into EMT‐6 (breast cancer tumor cells), and an 86% increase in the long‐term survival of the animals was proven.…”
Section: Introductionmentioning
confidence: 99%
“…Metal nanoparticles (NPs) in the tumor volume can serve as sensitizers for enhancing radiotherapy (RT) efficiency. [1][2][3][4][5][6][7][8][9][10] The in the tumor cell viability compared to untreated cells. [17] In a follow-up study, they also performed similar experiments with Au (diameter of 2-13 nm) and Fe (diameter of ≈14 nm) NPs, noting a 90% and 75% reduction in tumor volume, respectively while irradiation in the absence of NPs resulted in only an 18% reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, intracellular Au–Fe 3 O 4 or Pt–Fe 3 O 4 NHDs fostered the MCF-10A MCS growth, which is mainly due to the antioxidant caffeic acid ligands acting as ROS scavengers. Since caffeic acid is poorly soluble in water and therefore not suitable for medical application, the fusion of the antioxidant caffeic acid with redox-active Au-Fe 3 O 4 and Pt–Fe 3 O 4 NHDs is tailored for nanoantioxidant therapy as being bioavailable and as acting as a radioprotective antioxidant in healthy cells. , The antioxidant effect of caffeic acid depends on the intracellular ROS concentration. Cancer cells, for example, differ from healthy cells by their higher H 2 O 2 concentration.…”
Section: Resultsmentioning
confidence: 99%
“…To provide the Au–Fe 3 O 4 NHDs with a radioprotective function for healthy cells, the NHDs were functionalized with the natural ROS scavenger and anticancer drug caffeic acid . The combination of antioxidants and nanomaterials, also known as nano-oxidants, increases the bioavailability and biocompatibility of the radioprotective antioxidants. , Caffeic acid-functionalized Au–Fe 3 O 4 NHDs were shown to act as radioprotectors for nontumorigenic breast epithelial cells (MCF-10A) and as X-ray dose enhancers in breast cancer cells (MCF-7) in (2D) monolayer cell cultures . In recent studies, we showed that this effect was also preserved in (3D) multicellular spheroids. , …”
Section: Introductionmentioning
confidence: 99%
“…Adapted with permission. [545][546][547][548][549][550][551][552][553][554] Copyright, Wiley, American Chemical Society, and Elsevier.…”
Section: Nanomaterials For Radioprotectionmentioning
confidence: 99%